STUDY OF PARALINGUISTIC DEVICES IN MODERN LINGUISTICS - M.J, Ortiqova (International Journal of Psychosocial Rehabilitation, 2020)
In this article we will try to consider some methodological principles and features of teaching a foreign language in a technical university, based on the criteria for the development of professional competence.Knapp and Hall discuss several ways that nonverbal messages function in conjunction with the verbal ones.4 Nonverbal behavior substitutes, complements, accents, regulates contradict the spoken message. Substitution of a nonverbal message occurs when we use a nonverbal cue instead of a verbal one as when a language teacher gives the thumbs up signal to a student for using the correct verb tense. A nonverbal message complements the spoken word when it completes or supplements it as is the case when the words, “good job” are accompanied by the teacher’s smile in praising students’ group work. Accenting occurs when the speaker stresses a specific word in the message. An emphasis on the word, small in the sentence, “Please put yourselves into small groups for the next language activity,” indicates to the learners that less than four or five students per group is indicated. Nonverbal messages also regulate conversational flow as is the case with the teacher who nods her head as a student is speaking to encourage more talk, or the learner who is working in a group and who leans forward and inhales, signaling that he would like his turn to speak. Lastly, nonverbal cues contradict spoken messages when the verbal and nonverbal interpretations of the message are at odds with each other, as exemplified by the language learner who says, “I love grammar, Dr. Gregersen!” but whose voice makes me believe it is the last thing they would want to be spending their time on. Communication takes various forms, one of which is oral or speech. However, when people speak, they normally do not confine themselves to the mere emission of words. Furthermore, they also use their hands, (gestures), head moments, eyes (eye contact), lips (smile), bodily postures and symbols to communicate which always accompany oral discourse-intended or not.